Guidance for characterization of in‐house reference materials for light element stable isotope analysis. (1st September 2021) - Dunn, Philip J. H.; Malinovsky, Dmitry; Holcombe, Gill; Cowen, Simon; Goenaga‐Infante, Heidi
Abstract : Rationale: Preparation of in‐house reference materials (RMs) is an important aspect of light element stable isotope analysis. While some relevant information is available, there is as yet no clear set of guidelines available covering all aspects of in‐house production and characterization of RMs. Methods: To address this need, the experience of production of certified reference materials under accreditation to ISO 17034:2016 and ISO/IEC 17025:2017 has been distilled into guidance for production of in‐house RMs that are fit‐for‐purpose. Results: The guidance provided covers five areas: (i) planning; (ii) material considerations including preparation, packaging, and storage; (iii) measurements and assessments; (iv) value and uncertainty assignment; and (v) monitoring and use. Conclusions: In‐house RMs prepared by following this guidance can be used to provide traceability to measurement results when used for normalization or for quality control and/or assurance purposes.